PENERAPAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR PONTIANAK BARAT - Maharani, Dina; Asrori, Asrori; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe character education, both in planning, implementation, and evaluation in thematic learning at West Pontianak Elementary School. Using a qualitative approach with descriptive type. This research was conducted at SD Negeri 31 Pontianak Barat in January 2018. Data collection techniques used were observation, interviews, and documentation. The research instrument uses tools in the form of guidelines for observation, interviews, and document analysis. The results of the study showed that the application of character education through thematic learning at Pontianak Barat Elementary School showed an improvement in students through the learning process. Planning used in thematic learning consists of syllabus and lesson plans made by the teacher and has shown the integration of character education. In terms of implementation, the teacher implements it through learning activities, teachers instill these character values. Learning evaluation is done well through authentic assessment, which includes assessment of processes and assessment of learning outcomes. The assessment includes spiritual assessment, social assessment, knowledge assessment and skills assessment.Keywords: Character Education Application, Thematic Learning, Elementary School